Castles of Mistresses: Culinary Education in Agriculture and Vocational-Housework Schools in Lithuania in 1918–1940 - Minelgaitė-Plentienė, Justina (Acta humanitarica academiae Saulensis, 2024)
The article explores culinary education in special schools (schools for girls) in Lithuania from 1918 to 1940 by investigating the network of schools, their founders, the curriculum of culinary subjects, the typical students, and the likely significance of such education. From 1918 to 1940, a network of special schools which were also referred to as castles of mistresses was established in Lithuania where, along with the training of household chores, culinary education was also practiced. This network involved lower-grade agricultural schools as well as lower- and middle-grade schools of household chores. In terms of their specialization, schools had to train agricultural specialists – or craftswomen; however, the curriculum of the culinary section as well as the aspirations of all the schools were oriented towards modernizing the household culture along with the teaching of cooking the meals conforming to the contemporary gastronomy trends. These schools were established not only by State institutions, but also as public ventures. The schools which were run by women’s associations or Catholic organizations were nearly two times more numerous than the State-run schools (at a ratio of 17 to 9).A relatively significant share of the classes of culinary education in the general curriculum of the castles of mistresses highlights the exceptional attention to this field. The subject matter of the culinary classes was channeled in several directions which also reflected the general trends of the culinary culture of the time. The objective was the modernization, renewal and rationalization of the cooking environment, equipment, cooking accessories and crockery. Considering the still surviving relatively archaic aspects – which were still being sustained primarily in the countryside – students were gaining knowledge on laying the table, table decoration and the fundamentals of the table culture. Emphasis was being made on the integration of the science achievements in cooking, which was intended to cover the aspects of the nutrition value of the meals, proper digestion, and the inclusion of vitamins in the regular diet. Culinary education also highlighted the ideas of the use of the local produce. However, the general trends of the recipes were primarily targeting the ‘universal’ diet, and the manifestations of ‘gastro-national’ trends were more prominent in the cooking of the meals and beverages which were perceived as originally Lithuanian (these recipes were not very abundantly included in the programs). This trend was also manifested in the customs of fasting and the traditions of religious festivals.Although the numbers of the graduates of the castles of mistresses were relatively low, however, the sheer numbers cannot serve for defining the extent of the impact of these studies. When the students would come home or gain employment as cooks, chefs or mistresses in the households of the richer population, they were inherently sharing the experience they had accrued in the course of the years of studies. Consequently, the knowledge was being actively distributed. On the other hand, schools as centers of the culinary literacy were also having an impact on the local communities in which they were established. The students were fine-tuning their culinary knowledge at school canteens, and they were also taking a wide range of orders. Thus, the local communities were getting acquainted with the more modern culinary trends which had not yet been established in the provincial areas.
Keywords: culinary education; 1918–1940 Lithuania; agriculture school for girls; housework school for girls; culinary culture